A pilot study of bovine bone for orbital implants in rabbits - Shariff, Mohd Mansor (2006)
Objective: To assess the biocompatibility of bovine bone xenograft as ocular implants in rabbits. At the same time, to determine the presence of histopathological and clinical rejection towards bovine bone xenograft as ocular implant in rabbits. Methodology: Eviscerations with and without bovine bone orbital implantation were performed onto the right eye of 12 New Zealand white rabbits. Group A (n = 6) was eviscerated without implant whereas Group B (n = 6) was eviscerated with insertion of an orbital implant using bovine bone. Observation was done at day 1, day 7, day 14, day 28 and day 42. Serial clinical examination was done based on a few fixed criteria including rate of infection, implant migration, any evidence of wound breakdown and any restriction of intraocular movements. The implanted eyes were then enucleated on day 42. The enucleated eyes were sent for histopathological evaluation to record the type of inflammatory reaction and rate of fibrovascular ingrowth. Results: Serial clinical examination showed presence of minimal infection in all eyes both in the control group and the implanted first post operative day, which responded well with antibiotics. Infection occured after first post operative day but there was no evidence of orbital migration or extrusion of implant, wound breakdown, restriction of extra ocular movement, severe infection or any physical abnormality of implanted groups. Histopathological examination revealed good fibrovascular ingrowth in implanted groups, with minimal reaction of rabbit eye towards bovine bone implant. Conclusion: Orbital bovine bone implants was highly biocompatible with minimal infection during the early period and no evidence of clinical rejection. Histopathology examination supported the evidence of good fibrovascular ingrowth and minimal inflammatory reaction towards the implants. We can thus conclude that this bovine bone implant has a high potential for use clinically with the added advantage of being cost effective.